Euthanasia examined : ethical, clinical, and legal perspectives / edited by John Keown. - Keown, John (Cambridge University Press, 1995)
Whether euthanasia or assisted suicide should be legalised is one of the most pressing and profound questions facing legislators, health-care professionals, their patients and indeed all members of society. Regrettably, the debate is too often characterised by rhetoric rather than reason. This book aims to inform the debate by acquainting anyone interested in this vital question with some of the major ethical, legal and clinical and theological issues involved. The essays it contains are authoritative, balanced and readable: authoritative in that they have been commissioned from some of the world's leading experts; balanced in that they reflect divergent viewpoints (including a vigorous debate between two eminent philosophers); and readable in that they should be readily intelligible to the general reader. This accessible, fair and learned collection should enlighten all who wish to be better informed about the debate surrounding this momentous issue.